TEACHER'S BELIEFS IN USING SONGS IN TEACHING ENGLISH TO YOUNG LEARNERS : A Descriptive Study of an EYL Teacher in an English Course at Balai Bahasa UPI Bandung - Westhisi, Sharina M. (2015)
This background of the research is to identify the teacher's beliefs in using song as one of teaching media in teaching English to young learners which influence the teaching practices in the classroom. Hence, this present research aims to find out the beliefs of Indonesian teachers toward songs in teaching English to young learners and to find out the teacher's beliefs in using songs which influence the teaching practices in EFL classroom context. This research used a qualitative descriptive study design. The data were gained by conducting the interview and the classroom observation which involved an English teacher who had teaching experiences in teaching young learners. The data were analyzed through several steps adapted from Dörnyei (2011) which consist of transcribing, analyzing and classifying, and interpreting the data. The findings show that the teacher's beliefs in using songs in teaching English to young learners can influence the teaching practices in the classroom such as motivating the learners in the learning process, providing fun and joyful atmosphere, improving the learners' language skills, enriching the vocabulary, and empowering the grammar. Furthermore, in the teaching practices, the songs may be accompanied by the gestures and the pictures to give in-depth knowledge to the learners in comprehending the lesson. Thus, considering the findings, it is suggested that the teacher may employ the songs in the teaching process to create fun ambience in order to reduce the anxiety and the boredom of the learners. Meanwhile, it is also suggested that the learners can ask the teacher to provide the songs based on their needs and interests. Moreover, the level of the learners and the variety of the songs should be taken into account in further research regarding the teacher's beliefs in using songs in teaching English to young learners. Keywords: Teacher's beliefs, Young learners, Teaching practices, Using songs. ABSTRAK: Latar belakang penelitian ini adalah untuk mengidentifikasi keyakinan seorang guru dalam penggunaan lagu sebagai salah satu media pembelajaran dalam pengajaran Bahasa Inggris untuk anak-anak yang dapat mempengaruhi praktik mengajar di dalam kelas. Sehingga, penelitian ini bertujuan untuk mengetahui keyakinan guru-guru Indonesia terhadap penggunaan lagu dalam mengajarkan Bahasa Inggris untuk anak-anak dan untuk mengetahui keyakinan guru tersebut dalam penggunaan lagu yang dapat mempengaruhi praktik mengajar dalam konteks kelas EFL. Penelitian ini menggunakan desain penelitian deskriptif kualitatif. Data yang dikumpulkan melalui wawancara dan observasi kelas yang melibatkan seorang guru Bahasa Inggris yang mempunyai pengalaman dalam mengajarkan Bahasa Inggris untuk anak-anak. Data tersebut dianalisis melalui beberapa langkah yang diadaptasi dari Dörnyei (2011) yang terdiri dari menuliskan, menganalisis dan mengklasifikasikan, dan menginterpretasikan data tersebut. Hasil penelitian menunjukkan bahwa keyakinan guru tersebut yang menggunakan lagu dalam pengajaran Bahasa Inggris dapat mempengaruhi praktik mengajarnya di dalam kelas seperti memotivasi para siswa dalam proses pembelajaran, memberikan suasana belajar yang menyenangkan dan menggembirakan, meningkatkan kemampuan berbahasa, menambah kosakata, dan memperkuat tata bahasa. Selain itu, dalam praktik mengajar tersebut, lagu dapat disertai gerak tubuh dan gambar untuk memberikan penjelasan yang lebih dalam lagi bagi para siswa dalam memahami materi tersebut. Sehingga, dari hasil temuan penelitian ini, disarankan bahwa seorang guru dapat menggunakan lagu dalam proses mengajar untuk menciptakan suasana menyenangkan yang bertujuan untuk mengurangi rasa kecemasan dan rasa bosan yang dirasakan oleh para siswa. Sementara itu, disarankan juga bahwa para siswa dapat meminta guru mereka untuk menyediakan lagu-lagu yang sesuai dengan kebutuhan dan minat mereka. Selain itu, tingkatan siswa dan jenis-jenis lagu dapat menjadi bahan pertimbangan dalam penelitian berikutnya yang berkaitan dengan keyakinan guru terhadap penggunaan lagu dalam pengajaran Bahasa Inggris untuk anak-anak. Kata Kunci: Keyakinan guru, anak-anak, Praktik mengajar, Penggunaan lagu.